Human biological diversity - Brown, Daniel E., author.
1 online resource
Keywords: "Human Biological Diversity is an introductory textbook designed to cover the key contemporary topics in the study of human variation and human biology within the field of physical anthropology. Easily accessible for students with no background in anthropology or biology, this second edition includes two new chapters, one on human variation in the skeleton and dentition, and the other on tracing human population affinities. All other chapters have been fully updated to reflect advances in the field, and now include pedagogical features to aid the reader in their understanding. Written for an introductory level but still containing valuable information that will be of interest to students on upper level courses, Brown's textbook should be essential reading for all students taking courses on human variation, human biology, human evolution, race, the anthropology of race and general introductions to biological/physical anthropology"--